The Influence of Motor Vehicle Tax Collection System through Drive Thru Service on Taxpayer Compliance - Rakhmadhani, Vania (Jurnal Wacana Ekonomi, 2024)
This study aims to determine the effect of the motor vehicle tax collection system through drive-thru services on motor vehicle taxpayer compliance at SAMSAT Kota Cimahi. The research population is in the SAMSAT Kota Cimahi work area, using 100 samples with the Simple Random Sampling method. The data used in this study is primary data in the form of questionnaires distributed to motor vehicle taxpayers. The analysis used is simple linear regression. The results show that the motor vehicle tax collection system through drive-thru services has a positive impact on taxpayer compliance at SAMSAT Kota Cimahi.